Observed protection against SARS-CoV-2 reinfection following a primary infection: A Danish cohort study among unvaccinated using two years of nationwide PCR-test data - Daniela Michlmayr; Christian Holm Hansen; Sophie Madeleine Gubbels; Palle Valentiner-Branth; Peter Bager; Niels Obel; Birgitte Drewes; Camilla Holten Møller; Frederik Trier Møller; Rebecca Legarth; Kåre Mølbak; Steen Ethelberg (Elsevier, 2022)
Summary: Background: The level of protection after a SARS-CoV-2 infection against reinfection and COVID-19 disease remains important with much of the world still unvaccinated. Methods: Analysing nationwide, individually referable, Danish register data including RT-PCR-test results, we conducted a cohort study using Cox regression to compare SARS-CoV-2 infection rates before and after a primary infection among still unvaccinated individuals, adjusting for sex, age, comorbidity and residency region. Estimates of protection against infection were calculated as 1 minus the hazard ratio. Estimates of protection against symptomatic infections and infections leading to hospitalisation were also calculated. The prevalence of infections classified as symptomatic or asymptomatic was compared for primary infections and reinfections. The study also assessed protection against each of the main viral variants after a primary infection with an earlier variant by restricting follow-up time to distinct, mutually exclusive periods during which each variant dominated. Findings: Until 1 July 2021 the estimated protection against reinfection was 83.4% (95%CI: 82.2-84.6%); but lower for the 65+ year-olds (72.2%; 95%CI: 53.2-81.0%). Moderately higher estimates were found for protection against symptomatic disease, 88.3% overall (95%CI: 85.9-90.3%). First-time cases who reported no symptoms were more likely to experience a reinfection (odds ratio: 1.48; 95%CI: 1.35-1.62). By autumn 2021, when infections were almost exclusively caused by the Delta variant, the estimated protection following a recent first infection was 91.3% (95%CI: 89.7-92.7%) compared to 71.4% (95%CI: 66.9-75.3%) after a first infection over a year earlier. With Omicron, a first infection with an earlier variant in the past 3-6 months gave an estimated 51.0% (95%CI: 50.1-52.0%) protection, whereas a first infection longer than 12 months earlier provided only 19.0% (95%CI: 17.2-20.5%) protection. Protection by an earlier variant-infection against hospitalisation due to a new infection was estimated at: 86.6% (95%CI: 46.3-96.7%) for Alpha, 97.2% (95%CI: 89.0-99.3%) for Delta, and 69.8% (95%CI: 51.5-81.2%) for the Omicron variant. Interpretation: SARS-CoV-2 infection offered a high level of sustained protection against reinfection, comparable with that offered by vaccines, but decreased with the introduction of new main virus variants; dramatically so when Omicron appeared. Protection was lower among the elderly but appeared more pronounced following symptomatic compared to asymptomatic infections. The level of estimated protection against serious disease was somewhat higher than that against infection and possibly longer lasting. Decreases in protection against reinfection, seemed primarily to be driven by viral evolution. Funding: None.